The effects of robot-assisted gait training combined with non-invasive brain stimulation on lower limb function in patients with stroke and spinal cord injury: A systematic review and meta-analysis - Kuwahara, Wataru; Sasaki, Shun; Yamamoto, Rieko; Kawakami, Michiyuki; Kaneko, Fuminari (Frontiers in Human Neuroscience, 2022)
Objective: This study aimed to investigate the effect of robot-assisted gait training (RAGT) therapy combined with non-invasive brain stimulation (NIBS) on lower limb function in patients with stroke and spinal cord injury (SCI). Data sources: PubMed, Cochrane Central Register of Controlled Trials, Ovid MEDLINE, and Web of Science were searched. Study selection: Randomized controlled trials (RCTs) published as of March 3, 2021. RCTs evaluating RAGT combined with NIBS, such as transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS), for lower limb function (e.g., Fugl-Meyer assessment for patients with stroke) and activities (i.e., gait velocity) in patients with stroke and SCI were included. Data extraction: Two reviewers independently screened the records, extracted the data, and assessed the risk of bias. Data synthesis: A meta-analysis of five studies (104 participants) and risk of bias were conducted. Pooled estimates demonstrated that RAGT combined with NIBS significantly improved lower limb function (standardized mean difference [SMD] = 0.52; 95% confidence interval [CI] = 0.06–0.99) but not lower limb activities (SMD = -0.13; 95%CI = -0.63-0.38). Subgroup analyses also failed to find a greater improvement in lower limb function of RAGT with tDCS compared to sham stimulation. No significant differences between participant characteristics or types of NIBS were observed. Conclusion: This meta-analysis demonstrated that RAGT therapy in combination with NIBS was effective in patients with stroke and SCI. However, a greater improvement in lower limb function and activities were not observed using RAGT with tDCS compared to sham stimulation.